Fourteenth General Review of Quotas : Possible Elements of a Compromise. (Policy Papers; Policy Paper ;, 2010)
The IMFC in its April 2010 Communique pledged to complete the 14th Quota Review before January 2011 in line with the parameters agreed in Istanbul. The Committee of the Whole (COW) has since continued its work aimed at developing proposals that could command broad support. At its most recent meeting in September, there was a shared commitment to reaching an agreement within the agreed timetable but views remained divided on many issues. To facilitate progress towards the agreed goal, this paper suggests possible elements that could help form the basis for an agreement. These elements seek to build on the discussions to date and balance the diverse views that have been expressed. Inevitably, they will not fully meet the preferences or priorities of any individual member, and difficult compromises will be required from all sides if an agreement is to be reached.